SOCIAL ACCOUNTING: AN INVITATION TO THE ACCOUNTING PROFESSION. - Cooper, W. W. (The Accounting Review, 1949)
Abstract The article presents views of the author on accounting participation. To date this work has progressed almost entirely without participation from accountants. This lack of participation has, I think, been unfortunate. Accounting participation might have served to accelerate certain developments. It should not have taken so long to realize, as scholar Andrew Hagen notes that national-income measurement is best thought of as double-entry bookkeeping, a perception that at once made clear that the exact relationship between income and output. Moreover, the process of analysis has not been carried through to its ultimate conclusion. It is particularly deficient on the balance-sheet and especially the equity, side. In hands of economists it was only natural that emphasis should rest on income measurement. Only recently and imperfectly, has attention begun to be devoted to the balance sheet. To date, however, resolution to the equity accounts hits not been successfully carried out. It is difficult to believe that this balance sheet backwardness would have occurred if accountants had participated more systematically in these developments.